مفھوم الامانة في التراث الأدبي للامام علي ( علیھ السلام ) - دراسة تحلیلیة - أ.د. حمیدة صالح البلداوي (College of Education for Women, 2019)
the boot of honesty in the dictionary the term linguistic and religious heritage, literary and Islamic Sufi thought, and concept in the literature of Imam Ali, peace is upon him. And studied the summary first concerns its presence in the literature and implications and directions, either the second part, has cared for the analytical study has found research that safe weight was the counterpart of the personality of the Imam accompanied the character most prominent in his character, namely, (courage), it has struggled to deliver a impact of humanity in his time and after the word and deed, It was based on the imagination in the formation of images sensual and intellectual, to his persuasion of the evidence and arguments, which was adopted methods of art, including condensation and brevity and narrative including the metaphor and metonymy and bilateral discrepancy, including the rhythm Pacific report, ie, the wisdom of the rhythm of higher rebuke and violent tastefully artistic high to meet the biography of his life the confluence of thought and imagination and passion.